2011
DOI: 10.1097/ccm.0b013e31821858a0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two different electronic health record user interfaces on intensive care provider task load, errors of cognition, and performance*

Abstract: A novel user interface was designed based on the information needs of intensive care unit providers with a specific goal of development being the reduction of task load and errors of cognition associated with filtering, extracting, and using medical data contained within a comprehensive electronic medical record. The results of this simulated clinical experiment suggest that the configuration of the intensive care unit user interface contributes significantly to the task load, time to task completion, and numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
169
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(179 citation statements)
references
References 32 publications
1
169
1
8
Order By: Relevance
“…A full description and additional screen shots of the existing EMR environment has been previously published [25]. …”
Section: Description Of the Pre-existing Emrmentioning
confidence: 99%
See 1 more Smart Citation
“…A full description and additional screen shots of the existing EMR environment has been previously published [25]. …”
Section: Description Of the Pre-existing Emrmentioning
confidence: 99%
“…Concept orientated views such as these have been demonstrated to improve clinician understanding and decision making in other settings [24]. In simulated ICU settings AWARE has been demonstrated to improve efficiency, reduce clinician cognitive load and errors [25]. The purpose of the current study was to test the safety, efficacy and acceptance of AWARE in the clinical ICU setting.…”
Section: Introductionmentioning
confidence: 97%
“…The system may respond to their needs better, and hence is perceived as more accessible to them. Research has shown that successful implementation and meaningful use of an EHR are more likely when the system is more intuitive (easily operated), when it is made to fit clinical workflow and productivity, when initial as well as on-going training is provided, when clinicians are involved in defining their department-specific needs, when the design is novel and appropriate, where a realistic timetable is made using an assessment of the change-capability of the organization, and where effective knowledge governance practices are implemented [55,65,66].…”
Section: Insertmentioning
confidence: 99%
“…The information overload becomes a hindrance to the effective use of EMRs, which may lead to reduction in performance and alter patient safety. 23 Thus, not only is implementation of an automated electronic note search strategy to identify a patient's baseline comorbidities useful in medical research, but early identification of the comorbidities from the EMR might also be helpful for the efficient treatment of patients.…”
mentioning
confidence: 99%